KESERIUSAN MEMBACA TANPA PEMAHAMAN: STUDI KUALITATIF KESULITAN LITERASI SISWA SEKOLAH DASAR - Syaikhu, Ach; Ghina, Nabila Nilna (Universitas Al Falah As Sunniyah Kencong Jember (UAS Press), 2025)
This study aims to describe the difficulties faced by elementary school students in improving their literacy skills and to analyze the contributing factors. The research was conducted at SDN Bremi II, Krucil Subdistrict, Probolinggo Regency, using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The findings show that although students appeared serious and enthusiastic during reading activities in class, they still struggled to fully comprehend the meaning of texts. The main obstacles included limited vocabulary mastery, difficulty in interpreting implicit meanings, distractions caused by excessive gadget use, and the lack of varied and engaging reading materials. Additionally, the home environment provided minimal support for literacy development. These findings highlight the need to implement a multiliteracy approach, which emphasizes the ability to understand meaning through various forms of texts and media. Strategic efforts involving teachers, schools, parents, and the community are essential to create a more supportive literacy environment that fosters comprehensive literacy development in students.